Enhancing Writing Skill of Tourism and Management Business Students through Mind Mapping - Nurhalimah Nurhalimah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2019)
The study identifies appropriate Mind Mapping techniques to enhance the Tourism and Business Management Students’ writing ability. This particular research was categorized as action research which consists of some steps namely: planning, acting, observing, and reflecting. There were two kinds of data used in this research, qualitative data and quantitative data. The qualitative data were gained from classroom observation and interview and transformed into field notes and interview transcripts by using qualitative data analysis. The implementation of mind mapping as one of techniques successfully improved students’ ability and motivation in learning writing. Mind mapping helped the students in generating and developing their ideas and help them easily in way of collecting information in writing descriptive text about tourism destination.